A meta-analysis of agricultural conservation intentions, behaviors, and practices: Insights from 35 years of quantitative literature in the United States. (1st December 2022) - Lu, Junyu; Ranjan, Pranay; Floress, Kristin; Arbuckle, J.G.; Church, Sarah P.; Eanes, Francis R.; Gao, Yuling; Gramig, Benjamin M.; Singh, Ajay S.; Prokopy, Linda S.
Abstract: Conservation practices (CPs) are integral to maintaining the long-term viability of agro-ecological systems. Because farming systems and farmers' values and attitudes are heterogeneous, factors that consistently predict conservation behaviors remain elusive. Moreover, heterogeneity is present among studies regarding the type of CPs examined, and whether behavioral intentions or actual behaviors were measured. This study considers the characteristics of each CP, and whether a given study measured behavioral intention or actual behavior, to better understand farmers' adoption of CPs. We reviewed and analyzed 35 years (1982–2017) of quantitative conservation adoption literature in the United States. We categorized CPs based on their primary purpose, the type of benefit they provide, and whether they are operational or structural. We also examined the following five CPs: conservation tillage, buffers or borders, soil testing, grassed waterways, and cover crops. In our behavioral intention and actual behavior analysis, we found that attitudinal factors predicted both conservation intention and action (actual behavior), whereas current or previous use of practices only influenced actions, not stated conservation intentions. In our analysis focusing on CP characteristics, we found that having specific knowledge about and positive attitudes toward the CP, adoption of other CPs, seeking and using information, larger farm size, and vulnerable land predicted actual adoption across nearly all CP categorizations. Nuances emerge when comparing predictors of CPs that share a particular characteristic. For example, we found farm characteristics to be comparatively more important in predicting adoption of soil management CPs than nutrient and livestock management CPs, and farmers' stewardship identity to be more important for permanent practices than operational practices. Highlights: Paying attention to practice characteristics is important to explain adoption. Vulnerable land and knowledge specific to practices consistently predicted adoption. Adjacency to waterbody predicted adoption of practices providing off-farm benefits. Having a positive attitude more important for operational than permanent practices.